Promoting the role of political theory journals in protecting the Party’s ideological foundation and refuting wrong and hostile viewpoints - PHẠM THỊ THU HUYỀN (Political Theory Journal, 2026)
Promoting the role of political theory journals in protecting the Party’s ideological foundation and refuting wrong and hostile viewpoints is a fundamental task and an urgent requirement. The article analyzes the role of political theory journals in protecting the Party’s ideological foundation and refuting wrong and hostile viewpoints; on that basis, it outlines solutions to help improve the role, position, and communication efficiency of political theory journals, firmly consolidating the Party’s ideological foundation in the new situation.